Search for Scutellonema bradys resistance in yams (Dioscorea spp.) - Kwoseh, C.K.; Plowright, R.A.; Bridge, J.; Asiedu, Robert (African Journals Online, 2007)
A study to examine variability in susceptibility of yams to Scutellonema bradys and to identify possible sources of resistance in Ghanaian yam germplasm (Dioscorea spp.) for use in yam improvement programmes, particularly, in West Africa was undertaken. Pot and field screening methodologies were used. In general, S. bradys and dry rot of tuber symptoms as well as tuber cracking increased during the storage period. The study showed a positive correlation between visual nematode damage and population densities in yam tubers. There was also a linear relationship between dry rot disease and tuber cracking at harvest and during storage. This confirms that S. bradys causes dry rot of tubers resulting in external cracking of yam tubers. Positive linear relationship was also observed between yam tuber weight loss and dry rot disease indicating that dry rot disease may have contributed to the tuber weight loss. Therefore, tuber dry rot symptoms caused by S. bradys of yams could be used to discard susceptible yams at harvest and after a period of storage. However, there was no linear relationship between nematode population densities in yam tubers and roots, therefore, a root protocol cannot be used for assessing resistance in yams as it could lead to misclassification. The yam germplasm screened, reaffirmed resistance to S. bradys in Dioscorea dumetorum var. Nkanfo and D. cayenensis var. Afun.